Strategi Pelestarian Kesenian Tradisional Dongkrek Melalui Kegiatan Ekstrakurikuler - Titalia D Rahmasari; Bagas N Parahita; Danang Purwanto (UIN Fatmawati Sukarno Bengkulu, 2023)
Based on data from the Central Bureau of Statistics for 2021, the comparative results of the Indonesian people's interest in watching dance are still very low compared to their interest in watching film and music. This is also felt by the fate of Dongkrek Art, which is currently on the verge of worry because every year there is always news of the lack of participation of the younger generation. So efforts to preserve this art involve students in Dongkrek Art activities. Specifically, this research was conducted to examine the cultural strategy implemented by Balerejo 1 Public Middle School, Madiun Regency in preserving Dongkrek Art through extracurricular activities. With an analysis of cultural strategy theory by Van Peursen it was chosen because it helps modern humans to be more aware of their culture. This research methodology is qualitative with a case study approach. The informants in this study were the Dongkrek Arts teacher, the school principal, and members of the Dongkrek team, students of Balerejo 1 Middle School. The results of the study show that at the mystical stage, people believe that to expel pageblug they have to do the Dongkrek traditional art. Then, the ontological stage of the school began to introduce Dongkrek Art through learning materials as a symbol of cultural heritage. The community functionalist stage begins to develop Dongkrek Art into an attractive appearance with an innovation and relationship strategy. The results of this study are expected to be a source of reference for further research and become teaching materials related to Indonesian culture.